Osteomimetic bioceramic scaffolds with high-fidelity human-bone features produced by rotational printing - Shumin Pang; Dongwei Wu; Dorian A H Hanaor; Astrid Haibel; Jens Kurreck; Aleksander Gurlo (International Journal of Extreme Manufacturing)
Scaffolds that emulate the architecture of human bone, combined with strong mechanical stability and biocompatibility, are vital for promoting effective bone tissue regeneration. However, most existing bone-mimetic scaffolds fall short in reproducing the intricate hierarchical structure of human bone, which restricts their practical application. This study introduces a novel strategy that combines rotational three-dimensional (3D) printing technology and sponge replication technique to fabricate bone-mimetic scaffolds based on composite materials comprising copper-substituted diopside and biphasic calcium phosphate. The scaffolds closely mimic the structure of human bone, featuring both cancellous and cortical bone with Haversian canals. Additionally, the scaffolds exhibit high porosity and transport capacity, while exhibiting compressive strength that is on par with human bone under both axial and lateral loads. Moreover, they demonstrate good biocompatibility and the potential to induce and support osteogenesis and angiogenesis. The scaffolds produced here present a pathway to remediating particularly large bone defects. Given their close resemblance to human bone structure and function, these scaffolds may be well-suited for developing in vitro bone disease models for pharmaceutical testing and various biomedical applications.